The Answering of Wh-Questions In Newswriting Class of Students Academic Year 2021 Universitas PGRI Sumatera Barat - Autila, Rani (Jurnal Ilmiah Mandala Education (JIME), 2024)
The purpose of this study was to understand how journalism students apply the 5w 1h response in their news writing. This study is a qualitative study. The data source of this study is the thematic text in the mid-semester exam of journalism students in 2021.Data was collected by analyzing the students' test text using the document checklist.  Let it be, there are six uses to be seen, the answers being what, who, where, when, why and how. The results showed that out of 16 news tests taken by students, only 6 students fully answered factor 5w 1h. While the other 10 people did not answer all the items 5w 1h in their article, 2 people did not answer how, 4 people did not answer why, 1 person did not answer who, 4 people did not answer when. Meanwhile, everyone answers what and where. The data reveal why these ten news reports were incomplete, because their reports focused not on a single event but on two or three events that they mentioned in their reports. These students do not start the newsletter with important information but discuss other related topics besides current events. As a result, the discussion in the newsletter is not focused and therefore the 5w 1h factor is no longer taken into account.